The Emerging Entrepreneurial Students for being New MSME Business Actors in Bandung, Indonesia (Case Study of Private University Students in Bandung City) - DA Samoedra, Artarina; Junivans Sugiarto, Suggy; Firzandi, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship is a catalyst for economic growth and nationalist competitiveness. The problem of mindset or intention in entrepreneurship does not just come even though the candidates and entrepreneurs even though they have been given entrepreneurship and capital training. The purpose of this study is to examine the influence of entrepreneurial intentions seen from the factors of psychological capital and human capital itself. The research method used is quantitative with a questionnaire and by using path analysis. The results of this study are psychological capital and human capital contributed influence to entrepreneurial intention.